Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd006850.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Braces for idiopathic scoliosis in adolescents

Abstract: There is very low quality evidence in favour of using braces, making generalization very difficult. Further research could change the actual results and our confidence in them; in the meantime, patients' choices should be informed by multidisciplinary discussion. Future research should focus on short and long-term patient-centred outcomes, in addition to measures such as Cobb angles. RCTs and prospective cohort studies should follow both the Scoliosis Resarch Society (SRS) and Society on Scoliosis Orthopaedic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 138 publications
1
40
0
Order By: Relevance
“…23 girls and 7 boys were included. The mean age at radiological examination was 11 [range [8][9][10][11][12][13][14]. 10 were classified Risser 0 or 1, 7 were Risser 2, 8 were Risser 3 and 5 were Risser 4.…”
Section: Imaging Protocol and 3d Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…23 girls and 7 boys were included. The mean age at radiological examination was 11 [range [8][9][10][11][12][13][14]. 10 were classified Risser 0 or 1, 7 were Risser 2, 8 were Risser 3 and 5 were Risser 4.…”
Section: Imaging Protocol and 3d Modelingmentioning
confidence: 99%
“…The effect of bracing in idiopathic scoliosis has been evaluated in our series and essentially in the AP plane by means of global statistics [2][3][4][5][6][7][8]. However, the different curve topology and severity, different brace concepts and designs should not be analyzed together as this could lead to controversial conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Although research is still being conducted on the effects of physiotherapy 2 for scoliosis, bracing is recognized to stop progression 3 during the pubertal growth spurt. Now, with the newest Chêneau style computer-aided design/ computer-aided manufacturing (CAD/ CAM) bracing under certain circumstances the potential exists to improve curvature radiologically and visually 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Two publications reported bracing protocols that lasted up to 4 years and required the brace to be worn for 23 hours per day. 11,12 The effectiveness of bracing protocols is unclear, 13 although a recent trial reported by Weinstein et al 14 suggests that there is promise of efficacy.…”
Section: Rationale For Treatmentsmentioning
confidence: 99%